(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The "SPARQL Protocols as well as RDF Query Language" allows users to query information from a database or any other data source that can be mapped to RDF. The SPARQL standard, created and supported by the W3C, allows developers and users to concentrate on whatever they wants to know instead of how a database is organized. The proposed paper presents a Job Search Ontology to help the employers, by recommending the most eligible candidates for a particular job in IT domain and, on the other hand, to propose jobs to the aspiring candidates, matching their profiles with the existing job offers. This paper also discussed the continuous demand for qualified candidates in the Information Technology (IT) domain has empowered the use of e-Recruitment tools, which are becoming more and more exploited at the expense of the traditional methods in this paper. The major purpose of this research is to create an ontologies using the Protégé ontology construction tool, which is then used to run Simple Protocols as well as RDF (Resource Description Framework) Query Language (SPARQL) queries on it. This proposed system utilized Apache Jena Fuseki Server for execution of SPARQL queries for Job Search Ontology and it is very useful in upcoming days.